Boron Lewis Acid‐Catalyzed Hydroboration of Alkenes with Pinacolborane: BArF3 Does What B(C6F5)3 Cannot Do!1. Issue 39 (12th August 2016) - Yin, Qin; Kemper, Sebastian; Klare, Hendrik F. T.; Oestreich, Martin
Abstract: The transition‐metal‐free hydroboration of various alkenes with pinacolborane (HBpin) initiated by tris[3, 5‐bis(trifluoromethyl)phenyl]borane (BAr F 3 ) is reported. The choice of the boron Lewis acid is crucial as the more prominent boron Lewis acid tris(pentafluorophenyl)borane (B(C6 F5 )3 ) is reluctant to react. Unlike B(C6 F5 )3, BAr F 3 is found to engage in substituent redistribution with HBpin, resulting in the formation of Ar F Bpin and the electron‐deficient diboranes [H2 BAr F ]2 and [(Ar F )(H)B( μ ‐H)2 BAr F 2 ]. These in situ‐generated hydroboranes undergo regioselective hydroboration of styrene derivatives as well as aliphatic alkenes with cis diastereoselectivity. Another ligand metathesis of these adducts with HBpin subsequently affords the corresponding HBpin‐derived anti ‐Markovnikov adducts. The reactive hydroboranes are regenerated in this step, thereby closing the catalytic cycle. Abstract : Scrambled puzzle : Unlike B(C6 F5 )3, the rarely used boron Lewis acid BAr F 3 (Ar F =3, 5‐bis(trifluoromethyl)phenyl) initiates the catalytic hydroboration of various alkenes with pinacolborane. No assistance of an external base is required. An unexpected mechanism accounts for this striking reactivity difference leading to a cis ‐selective hydroboration as opposed to typical Lewis acid‐catalyzed hydrometalation reactions.